Understanding farmers’ adaptation to water scarcity: a case study from the western Nile Delta, Egypt - Ghazouani, Wafa; Molle, Francois; Swelam, A.; Rap, Edwin; Abdo, A. (International Water Management Institute, 2014)
This study was undertaken to analyze farmers’ adaption to water scarcity in the command area of a secondary canal in the Nile Delta of Egypt. The results revealed that farmers’ responses were driven by a multiplicity of factors, beyond water scarcity or profit maximization. These additional factors include food security of the family, risk management, social capital and history of farmers, and most unexpectedly the collective dimension of crop choice. The findings of this study expose the limitations of projects, modeling exercises or policy recommendations that are too often based on the oversimplified view of profit maximization as the basis of farming system dynamics.